German Letters of Alexander Serov 1858–1859 in the Manuscript Department of the St. Petersburg Conservatory (From the Composer’s Unpublished Legacy) - Anastasia S. Voitseshko; Zivar M. Guseinova (Современные проблемы музыкознания)
The epistolary legacy of Alexander Nikolaevich Serov contains rich material for the study of his work, personality — and, more broadly, the history of Russian music in the second half of the 19th century as a whole. The article is dedicated to the letters that the composer wrote to his mother during his first trips abroad (1858–1859). At the same time, he published correspondence in the form of “traveler’s notes” in the magazine Music and Theatre Herald. Both the mother’s letters and the correspondence published in the magazine record impressions of the trip, including Serov’s acquaintance with Franz Liszt, Hector Berlioz and Richard Wagner, but differ significantly in detail. The appendix to the present article presents five and previously unpublished letters from the composer to his mother, which were written during his trip to Germany (1858–1859). Keywords: Alexander Nikolaevich Serov, epistolary legacy, letters of 1858–1859, Germany, the magazine Music and Theatre Herald For citation: Voitseshko, A. S., & Guseinova, Z. M. (2025). German Letters of Alexander Serov 1858–1859 in the Manuscript Department of the St. Petersburg Conservatory (From the Composer’s Unpublished Legacy). Contemporary Musicology, 9(2), 71―105. https://doi.org/10.56620/2587-9731-2025-071-105